An effective discharge method for condensed water inside the GDL using pressure gradient of a PEM fuel cell. (June 2015) - Lee, Nam Woo; Kim, Sung Il; Kim, Young Sang; Kim, Sae Hoon; Ahn, Byung Ki; Kim, Min Soo
Abstract: When a fuel cell vehicle is operated in low temperature right after starting up, performance drop due to flooding often occurs in the catalyst layers, gas diffusion layers (GDL), and gas channels of the fuel cell. It is not easy to remove condensed water from the catalyst layer and GDL at low temperature because of surface tension between water and pores of the catalyst layer and GDL. In order to solve this problem, "low air S.R. (Stoichiometry Ratio) operation" using pressure gradient between the cathode catalyst layer and cathode side gas channel was suggested and experimentally verified. The main idea of the low air S.R. operation was lowering the air flow rate supplied to the cathode while maintaining current output from the fuel cell. From the test results including transparent fuel cell test, it was found that this idea was effective in discharging the condensed water inside the cathode catalyst and GDL toward the gas flow channels in a flooding condition. Additionally, a degradation test for the suggested method was conducted to check the effects on a service life of a fuel cell.